Caring capitalism : the meaning and measure of social value - Barman, Emily (Cambridge University Press, 2016)
"Companies are increasingly championed for their capacity to solve social problems. Yet what happens when such goods as water, education, and health are sold by companies - rather than donated by nonprofits - to the disadvantaged and when the pursuit of mission becomes entangled with the pursuit of profit? In Caring Capitalism, Emily Barman answers these important questions, showing how the meaning of social value in an era of caring capitalism gets mediated by the work of 'value entrepreneurs' and the tools they create to gauge companies' social impact. By shedding light on these pivotal actors and the cultural and material contexts in which they operate, Caring Capitalism accounts for the unexpected consequences of this new vision of the market for the pursuit of social value. Proponents and critics of caring capitalism alike will find the book essential reading"--